MAGNESIUM MEDICATION USE IN CARDIOLOGY PRACTICE - M. N. Mamedov (Российский кардиологический журнал)
This review focuses on the mechanisms of action and clinical effectiveness of Magnerot, or magnesium orotate, which is widely used in cardiac patients. Organic salt of magnesium orotate increases magnesium assimilability, improves vasodilatation and myorelaxation, and demonstrates antiarrhythmic and anti-ischemic effects. In cardiology practice, the scope of Magnerot use is relatively wide, from angina to heart failure treatment.